Chemical Recycling of PET Waste from Soft Drink Bottles to Produce a Thermosetting Polyester Resin - Abu Bakar, Dayang Ratnasari; Ahmad, Ishak; Ramli, Anita (Institut Kimia Malaysia, 2006)
Poly(ethylene terephthalate) or PET waste from soft drink bottles was subjected to recycling by glycolysis. Characterization and identification were performed by the conventional method of hydroxyl and acid values, Differential Scanning Calorimetry (DSC) and Frourier Transform Infra Red (FTIR) techniques. It was found that the glycolysed product consists mainly of bis(hydroxyethyl) terephthalate (BHET) and its dimer. The glycolysed product was later polyesterified with maleic anhydride and then cross linked with styrene to produce a formulation for the resin. FTIR spectra also revealed the cross linking process between the polyester chain and styrene monomer, resulted in a final product with high densities of cross-linkages to form a network polymer. The cured resin exhibited thermal stability due to its fully curing.